Change in land use and land cover affected by light rapid transit Jakarta, corridor Cawang – Bogor, Indonesia. (December 2019) - Azmi, M I; Widiatmaka; Munibah, K
Abstract: Change of land use and land cover caused by population growth and accessibility to transportation will decrease land availability for different purposes as well as land quality. Statistical data in DKI Jakarta Province shows that population growth in 2016 is 1.07%, this population growth is less than population growth during 2000 – 2010. This population growth decrease is affected by the community, which now choose to live in surrounding areas such as Bogor, Depok Tangerang, and Bekasi. This buffer area of Jakarta is developed to become a settlement and commercial area. The objective of this study is to analyze changes in land use and land cover in the area passed by Light Rapid Transit (LRT) Jabodebek in the corridor of Cawang – Bogor and to evaluate the impact of such change in environment. The study was conducted in the area passed by LRT Jabodebek corridor Cawang - Bogor. This study uses SPOT imagery of 2014 and 2018. Land use and land cover change resulting from classification were modelized using CA-Markov. The results of the study showed that open land decrease by 0.84%. The Settlement area and commercial area increase by 0.35% and 0.48%. Changed in land use and land cover was detected mostly caused by the development of the business regions. New commercial areas resulting from this process should be integrated into local transportation for increasing environmental efficiency.